Update on acute endovascular and surgical stroke treatment. (7th August 2012) - Kondziella, D.; Cortsen, M.; Eskesen, V.; Hansen, K.; Holtmannspötter, M.; Højgaard, J.; Stavngaard, T.; Søndergaard, H.; Wagner, A.; Welling, K.‐L.
<x xml:space="preserve">Abstract</x> Emergency stroke care has become a natural part of the emerging discipline of neurocritical care and demands close cooperation between the neurologist and neurointerventionists, neurosurgeons, and anesthesiologists. Endovascular treatment (EVT), including intra‐arterial thrombolysis, mechanical thrombectomy and angioplasty/stenting, is under rapid development. Although EVT has yet to be shown in randomized controlled trials to improve clinical outcome compared to intravenous thrombolysis, it is far better in achieving recanalization of occluded large cerebral vessels, which is crucial for rescuing the penumbra. Moreover, decompressive craniectomy is now a well‐established treatment option for malignant middle cerebral artery infarction and cerebellar stroke. Using a case‐based approach, this article reviews recent achievements in advanced treatment options for patients with acute ischemic stroke.